Kelet-Galícia 1918-1919 : egy Nyugat-Ukrán állam önállóságának létjogosultságáról - Polgár, Tamás (Közép-Európai Közlemények, 2012)
In the autumn of 1918, at the time of the disruption of the Austro-Hungarian Monarchy, a bitter struggle started between the Ukrainians and the Polish for the ownership of Galicia’s Eastern regions. In the rural parts of the economically underdeveloped region, the majority of the Greek Catholic Ukrainians was definite, while in the major cities, among them in the centre of Lemberg, Roman Catholic Polish made up the vast majority of the population, and also the Jewish were represented in a significant number. The ethnic-cultural and religious Polish–Ukrainian conflict soon became a social (rural vs. urban and workers vs. intellectual) conflict as well. As for the Polish, Eastern-Galicia was on the periphery, while for the Ukrainians it lay in the centre; at the time of the disintegration of Austria-Hungary they had the advantage, which, however, soon disappeared. The Great Powers also took part in the conflict, but without results due to the lack of knowledge about the local relations. The newly born West-Ukrainian Republic had no diplomatic chances, only the neighbouring Kiev Ukraine acknowledged it. The dispute was settled by arms and by the summer of 1919 all three territories claimed by the Rada –Eastern-Galicia, Subcarpathia and Northern-Bucovina –had been occupied by armies of other countries –Poland, Czechoslovakia and Romania.